Emerging cellular and pharmacologic therapies for acute respiratory distress syndrome. Issue 1 (February 2021) - Gonzalez, Hector; Horie, Shahd; Laffey, John G.
Abstract : Purpose of review: Advances in our understanding of the pathophysiology and biology of ARDS has identified a number of promising cellular and pharmacological therapies. These emerging therapeutics can modulate the immune response, reduce epithelial injury, target endothelial and vascular dysfunction, have anticoagulant effects, and enhance ARDS resolution. Recent findings: Mesenchymal stromal cell therapy shows promise in earlier phase clinical testing, whereas a number of issues regarding clinical translation, such as donor and effect variability, are currently being optimized to enable larger scale clinical trials. Furthermore, a number of promising mesenchymal stromal cell therapy clinical studies for COVID-19-induced ARDS are underway. Recent studies provide support for several emerging ARDS pharmacotherapies, including steroids, statins, vitamins, anticoagulants, interferons, and carbon monoxide. The history of unsuccessful clinical trials of potential therapies highlights the challenges to successful translation for this heterogeneous clinical syndrome. Given this, attention has focused on the potential to identify biologically homogenous subtypes within ARDS, to enable us to target more specific therapies, i.e. 'precision medicines'. Summary: Mesenchymal stromal cells, steroids, statins, vitamins, anticoagulants, interferons and carbon monoxide have therapeutic promise for ARDS. Identifying ARDS sub-populations most likely to benefit from targeted therapies may facilitate future advances.